KENDALI PENERANGAN RUMAH JARAK JAUH MENGGUNAKAN SHORT MESSAGE SERVICE (SMS) - Ahmadi, Aziz (Jurnal Neutrino, 2009)
In comunicating handphone/ponsel with microcontroller to be able to used as a instrument of long distance controller it is needed an interface that can synchronize both device so that it can mutually exchange data. Interface system in this research uses communication stripe port of data found on under part of handphone to be able to communicate with microcontroller serially.This tool is made by using controller of microcontroller as principal module, that will read SMS that step into handphone as a command in controlling to realize in mikrokontroler output, also command handphone to send sms output status reply to sender’s handphone. In this thesis it can be used most of all handphone types that has equiped AT command facilities with data cable spesification that related to instrument serially, while for controlling it can be used any handphone with SMS facilities. But it can only use XL and IM3 number for controlling. This tool has been tested by using 8 lamps with 220 volt, in which every lamp represents one output stripe as controlling on/off. the testing form is by trying to turn on or turn off all eight lamps, from the testing result it can be concluded that handphone can be accessed well by microcontroller pass through its serial data port so that can be used as a instrument of long distance controller.Key Words: Control, Lightness, Short Message Service (SMS)